PENGARUH LATIHAN PUSH-UP (GENGGAMAN DISAMPING BADAN) TERHADAP KECEPATAN PUKULAN GYAKUSUKI PADA ATLET SENIOR KARATE PEKERJAAN UMUM (PU) PARIT INDAH PEKANBARU - Widya Amalia; .Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrac: The problem in this research is the lack of ability to punch velocity gyakusuki on karate athletes PU Parit Indah Pekanbaru. At the time of making a strokeathletes gyakusuki are only three athletes who have a blow speed 90-105, based on the norms expressed less so. The shape of this research is the experimental treatment (Experimental). The independent variable was exercise Push Up (X) is the dependent variable speed drills punch (Y). With thetechnique total sampling is a sample of 6 people. Data were obtained and collected through preliminary tests and final tests before and after exercise push-up. Using the test instrument hit the tug, which aims to measure the speed of the arm and shoulder muscles. After that, the data is processed with statistical, normality test lilifors test at a significance level α (0.05). The hypothesis is their influence on the speed of punch gyakusuki.Based on the analysis of statistical data, there are an average of 91.67 Pree-test and post-test average rata110,33, then the data is normal. Based on t test analysis produces Tcalculated at 6.062 and Ttable at 1,943, meaning Tarithmetic> Ttable. Thus, there Effect of Exercise Push Up Againstpunch velocity gyakusuki on senior karate athlete Pu Parit Indah Pekanbaru.Keywords: Push-Up, Speed Sleeve and Shoulder Muscles